The dual role of glycogen synthase kinase-3 beta (GSK3β) in neurodegenerative pathologies: interplay between autophagy and disease progression - Alhassan, Hassan H.; Janiyani, Komal; Surti, Malvi; Adnan, Mohd; Patel, Mitesh (Frontiers in Pharmacology, 2025)
Glycogen Synthase Kinase-3 Beta (GSK3β), a multifunctional serine/threonine kinase, plays a central role in cellular signaling pathways and autophagy regulation, processes critical to neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, Huntington’s disease and Amyotrophic Lateral Sclerosis (ALS). Dysregulation of autophagy leads to the toxic accumulation of misfolded proteins and damaged organelles, contributing to neuronal loss in these disorders. This review explores the mechanistic interplay between GSK3β and autophagy, highlighting its modulation through key pathways, including mTOR, AMPK and Bcl-2 and its direct impact on autophagy-related proteins such as Beclin-1 and LC3. This review systematically discusses the disease-specific roles of GSK3β in autophagy dysregulation and protein aggregation, providing evidence from recent studies on neurodegenerative models. Additionally, therapeutic approaches targeting GSK3β are evaluated, including preclinical and clinical trials of GSK3β inhibitors and combination therapies with autophagy modulators, emphasizing their potential for improving neuroprotection and cellular homeostasis. Despite its promise, challenges such as off-target effects and pathway complexity remain significant. This review highlights the importance of GSK3β as both a therapeutic target and a biomarker, offering avenues for future research into selective GSK3β modulators that enhance autophagy and mitigate ND progression.